Temporal changes in the water quality of urban tropical streams: An approach to daily variation in seasonality - Bega, João Miguel Merces [UNESP]; Zanetoni Filho, José Antônio; Albertin, Liliane Lazzari [UNESP]; Oliveira, Jefferson Nascimento de [UNESP] (Oxford University Press (OUP), 2021)
Using water quality indices (WQIs) is one way to monitor watercourses for water quality. Currently, there is a lack of information about their behavior in the diurnal cycle because sampling is often carried out in the morning. Also, few articles focus on assessing the urban impact on the spatial variability of WQIs in tropical first-order streams. Such streams receive many pollutants varying in intensity according to population habits, justifying the possible diurnal variation in water quality in addition to climatic attributes. This paper aims to evaluate the fluctuations in Brazilian WQIs and their parameters (temperature, turbidity, total solids [TS], hydrogen potential, dissolved oxygen [DO], biochemical oxygen demand [BOD], total phosphorus [TP], total nitrogen [TN], and Escherichia coli) between the morning (8 AM), afternoon (2 PM), and night (7 PM) periods for an urban first-order tropical stream. Overall, the lowest DO concentrations and highest values of TS, turbidity, BOD, TP, TN, and E. coli were obtained in the morning, possibly representing population habits: the greatest generation of pollutants occurs overnight and in the early morning because there are clandestine domestic wastewater inputs into the stream, whose hourly periodicity generates a similar periodicity in the WQI of the evaluated stream. Although there was a significant variation in WQI average values between morning (15.50 ± 1.97) and afternoon (20.83 ± 5.42) only during the dry season (p < 0.05), different results were common throughout the day in all months, and the water quality was often classified in distinct categories: very bad, bad, and regular. Our findings present another dimension to be considered when assessing urban water quality, leading to direct benefits to the management and use of urban waters. Integr Environ Assess Manag 2022;00:1–12. © 2021 SETAC.